Peningkatan Kesadaran Masyarakat Terhadap Kesehatan Lingkungan di Kampung Gambiran RW 10 - Pramest, Yumna Rana; Wahyuningtyas, Sharasvia Intan; Amalia, Salsabilla Putri; Satria, Novaryan Anugrah; Riyanto, Rajiv Fadel; Wananta, Madya Rahmanda; Ramadhan, Alaufi Rizki; Asyam, Tegar Alif; Putri, Swidia Wiharema; Abdillah, Nailah Marwa; Widodo, Widodo (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Increasing public awareness of environmental health in Kampung Gambiran RW 10 has become a major challenge due to poor waste management, which poses a risk of environmental pollution. This issue is exacerbated by the lack of waste segregation at the source and the limited availability of efficient waste processing technologies. Therefore, this community engagement program aims to enhance public awareness and skills in waste management through the implementation of pyrolysis technology and vegetable planting using the polybag method. The methods employed in this program include a focus group discussion (FGD) with community leaders, field observations, socialization on pyrolysis and waste segregation, and a practical demonstration of polybag planting with the Women's Farmer Group (KWT). The results of this program indicate an increased understanding among residents regarding plastic waste management using pyrolysis technology, which enables the conversion of waste into oil as an alternative fuel. Additionally, the provision of waste segregation bags has encouraged the community to separate waste at the household level. Meanwhile, the polybag vegetable planting activity has provided a solution for utilizing limited land for household-scale urban agriculture, which is expected to improve food security and urban greening. The program culminated in the "Gambiran Waste Awareness" event, which included a parade and a recycled waste competition, fostering active community participation in maintaining environmental cleanliness. Overall, this initiative has yielded measurable positive impacts, both quantitatively, as reflected in the number of participants involved in socialization and practical activities, and qualitatively, through increased awareness and behavioral changes toward better environmental management.